ANALYSIS OF THE EFFECT OF INCOME DIVERSIFICATION ON BANK PERFORMANCE AND BANK RISK WITH OWNERSHIP STRUCTURE AS MODERATING VARIABLE IN DIGITAL BANKS IN INDONESIA - Endang Tri Widyarti; Desy Febriana Sari (Jurnal RAK (Riset Akuntansi Keuangan), 2022)
This study aims to analyze the effect of income diversification on performance and risk in digital banks, and examine the moderating role of the ownership structure variable as proxied by concentrated ownership of the effect of income diversification on bank performance as measured by ROA and Tobins's Q and bank risk as measured by Z. -Score on digital banks in Indonesia. The research data is taken from the financial statements of banks listed on the Indonesia Stock Exchange (IDX) for the period 2020-2021. The number of samples used in this study was 70 using purposive sampling technique. The analytical method used is Multiple Linear Regression and Moderated Regression Analysis. The results of this study state that income diversification has a positive and significant effect on bank performance as measured by ROA and Tobin's Q. Also, it has a positive and significant effect on bank risk as measured by Z-Score. In addition, this study shows that banks with concentrated ownership have a negative and significant effect in moderating the effect of income diversification on ROA. Meanwhile, banks with concentrated ownership are unable to moderate the effect of income diversification on Tobin's Q and Z-Score.